Our progressive economy is consistently bolstered by our international reputation as a peaceful and stable democratic nation : interview, The Honourable Kamla Persad-Bisseassar, SC, MP, Prime Minister of the Republic of Trinidad and Tobago - McAlpine, Jan (2013)
Addresses plans for strengthening and diversifying the economy away from its dependency on oil and gas reserves.